The Regulatory Framework and Policies for Advancing Green Logistics in Republic of Moldova’s Agri-Food Sector - Bulat, Veronica; Carp, Elena (Acta Universitatis Danubius. Œconomica, 2025)
This study examines how green logistics strategies and decision-making models can enhance the efficiency of the agri-food supply chain in the Republic of Moldova. It identifies major challenges, including high logistical costs, environmental impact, and limited market access, while highlighting the role of European policies and digital technologies in promoting sustainability. To address these issues, the research employs a structured decision-making approach, focusing on supplier selection and strategic business choices. A multi-method framework is utilized, integrating quantitative analysis, decision modelling, and policy assessment. The Global Utility Method (GUM) is applied to evaluate suppliers based on key criteria, ensuring an objective and systematic selection process. The findings indicate that incorporating structured decision-making enhances logistical efficiency, cost management, and sustainability in the agri-food sector. Furthermore, the study underscores the importance of digital transformation, environmentally responsible logistics, and data-driven procurement decisions in achieving long-term industry growth. By demonstrating the benefits of green logistics and analytical decision-making models, the research highlights their critical role in ensuring sustainable development, supply chain resilience, and economic competitiveness within Moldova’s agri-food industry.